PALYNOLOGICAL EVENTS OF THE TALANG AKAR FORMATION IN THE ON-SHORE AREA OF THE SOUTH SUMATRA BASIN - Eko Budi Lelono (Testing Center for Oil and Gas LEMIGAS, 2004)
South Sumatra has been well known as the one of the largest hydrocarbon producers in Indonesia. Due to its potentiality, South Sumatra has been explored since the Dutch era. Million barrels of oil have been pumped out from this area and many unpublished reports and papers have been made regarding the remaining reserve of this area. This study focuses on Talang Akar Formation which is considered as the main reservoir in South Sumatra. Talang Akar Formation is interpreted to be formed in a deltaic environment (De Coster, 1974). The deltaic sediment must have contained excellent palynomorph assemblage as demonstrated by the previous authors (Hasjim, 1993, Morley, 1995 and LEMIGAS 2001a, b and c). On the other hand, marine microfossils show poor recovery including foraminifers and nannoplankton. This condition is understandable as marine microfossils are difficult to develop in the transition environment. For this reason, palynology is intensively studied as a powerful tool to comprehend the stratigraphy of the Talang Akar Formation.The deposition of Talang Akar Formation was influenced by the tectonic event during Late Cretaceous to Early Tertiary which caused the occurrence of Semangko Dextral Fault (Suwidiyanto, 2003). This fault resulted in the formation of horst and graben which allowed sedimentation of Lahat Formation and the Lower Talang Akar Formation in the low topography. Subsequently, sea level increased rapidly drowning up the deposition center which resulted in the sedimentation of the Upper Talang Akar Formation and limestone Baturaja Formation (Suwidiyanto, 2003). Based on lithological character, Talang Akar Formation is separated into Great Sand Member (GRM) occupying lower part of this formation and Transition Member (TRM) situating in the upper formation. GRM was formed in the fluvial to delta plain environment, whilst TRM was deposited in delta plain to pro-delta environment (De Coster, 1974). The environmental change from fluvial-delta plain of GRM (non-marine) to delta plain-prodelta of TRM (nonmarine to transition) suggests the occurrence of transgressive phase. Palynologically, this change must be reflected in the palynological assemblage. In fact, TRM yields more brackish palynomorphs than those of GRM. In contrary, GRM especially those of river channel deposits are characterised by regular occurrence of riparian (freshwater) pollen such as Marginipollis concinus and Pandaniidites sp. (LEMIGAS, 2001a, b and c).Although palynological investigations were frequently conducted within the Talang Akar Formation, the results of these investigations were restricted on age interpretation and paleoenvironment analysis. There are more information can be obtained from the palynological data. Therefore, it is required extra efforts to elaborate data becoming useful information such as palynological event, sea level changes and paleoclimate. This study intends to explore the stratigraphy of the Talang Akar Formation based on its palynological and other micro-fossil content which focuses on palynological characteristic of the Talang Akar Formation, palynological event and other biostratigraphic information (zones, age and depositional environment).